ONE MAN’S TRASH, ANOTHER MAN’S TREASURE. ARCHITECTURAL CIRCUITS IN A GLOBAL CONTEXT - Vadstrup Holm, Iben (BDC. Bollettino Del Centro Calza Bini, 2013)
The world’s largest island, Greenland, is facing enormous challenges as the ice melts, minerals become available and new international industries and foreign cultures arises. Greenland calls for new solutions and the aim of the project One Man’s Trash, Another Man’s Treasure – developed in collaboration with Lise Birgens Kristensen at the School of Architecture Aarhus – is to explore how architecture can contribute to a positive sustainable development in Greenland. The development of the project started with a fascination of the circuits of nature – the biosphere and the mindset of the “industrial symbiosis” in Kalundborg – as an example on how waste from one industry can become the raw material of another. By interpretating these concepts into the field of architecture, the project demonstrates how architecture can be a link that connects flows of resources into programmatic, ecological and social circuits. In its overall form the project is an initiation of studies that indicate how architecture can be a tool to create sustainable design in cooperation with living resources, technology and humans beings in a network of mutually dependency.